2012
DOI: 10.1063/1.4773008
|View full text |Cite
|
Sign up to set email alerts
|

High efficient luminescence in type-II GaAsSb-capped InAs quantum dots upon annealing

Abstract: Polarization-resolved resonant fluorescence of a single semiconductor quantum dot Appl. Phys. Lett. 101, 251118 (2012) Optical cavity efficacy and lasing of focused ion beam milled GaN/InGaN micropillars J. Appl. Phys. 112, 113516 (2012) Competitive carrier interactions influencing the emission dynamics of GaAsSb-capped InAs quantum dots Appl. Phys. Lett. 101, 231109 (2012) Fluorescence quantum efficiency of CdSe/ZnS quantum dots embedded in biofluids: pH dependence J. Appl. Phys. 112, 104704 (2012) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…Previous results had shown that the incorporation of a high Sb content in the SRL extended the emission wavelength of InAs QDs to 1345 nm (at 15 K) and induced a type II band alignment, as revealed by the large radiative lifetime of 14.2 ns (further details of PL and time-resolved PL of these samples can be found in [19]). More important, the RTA retained the type II emission (radiative lifetime of 11.8 ns) while producing a significant enhancement of the PL, increasing both the integrated intensity (by a factor of 3.3) and monochromaticity (FWHM reduced from 97 meV to 32 meV, i.e., by 67%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous results had shown that the incorporation of a high Sb content in the SRL extended the emission wavelength of InAs QDs to 1345 nm (at 15 K) and induced a type II band alignment, as revealed by the large radiative lifetime of 14.2 ns (further details of PL and time-resolved PL of these samples can be found in [19]). More important, the RTA retained the type II emission (radiative lifetime of 11.8 ns) while producing a significant enhancement of the PL, increasing both the integrated intensity (by a factor of 3.3) and monochromaticity (FWHM reduced from 97 meV to 32 meV, i.e., by 67%).…”
Section: Resultsmentioning
confidence: 99%
“…In these images, the wetting layer (WL) and QDs can be clearly distinguished with a darker contrast than GaAs, while the capping layer exhibits a brighter contrast. Our measurement on more than 60 QDs [19] showed that the RTA gave way to an important reduction of the average height (from 3.3 ±0.6 to 2.3±0.4nm) together to an increase of the base diameter (from 16±4nm to 22±7nm). In addition, the thickness of the SRL was reduced by approximately 1 nm, i.e., from 6.5 to 5.5 nm in areas far from the QDs.…”
Section: Ctem Analysesmentioning
confidence: 98%
See 2 more Smart Citations
“…14 Rapid thermal annealing of these samples resulted in type-II QDs with highly efficient luminescence which are, nevertheless, not optimal candidates as laser gain material due to the type-II alignment. 15 The Sb incorporation method on the InAs nanostructures plays a crucial role in InAsSb QDs' great performance for optical applications. Previous papers reporting on the optical characterization of InAsSb QDs directly grown on GaAs addressed that, independent of the Sb beam flux used during growth, the emission was blueshifted with respect to the InAs QD reference ensembles (blueshift ranging from 42 to 106 meV).…”
Section: Introductionmentioning
confidence: 99%